FUNGSI AGIL DAN KEBERDAYAAN KELUARGA DI PERKOTAAN DAN PEDESAAN: KASUS KELUARGA DI KECAMATAN DUREN SAWIT DAN KECAMATAN JASINGA - Astriana Baiti Sinaga; Sumardjo Sumardjo (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2007)
Family has importanifimclions.for human development, and all functions must work properly. The effectiveness of functions determine family’s empowerment quality. In fact, some families failed to implement some of the functions, due to the influence of some factors. This research studied factors affected family's functions and empowerment, and develop model,for family empowerment. Data was collected in period of August-December 2006, involving Duren Saivil, of East Jakarta and Jasinga, of Bogor Regency. The four functions of family: adaptation, goal attainment, integration, and latency (AGIL) influence the family empowerment, and have a significant correlation between each other. The results of research indicate that each function is influenced differently in different area. The level implementation of adaptation, goal attainment, and latency function are low, but the integration function is in the middle level calegory in Duren Sawit and Jasinga. The family's empowerment is in middle level category in Duren Sawit and Jasinga.